Parenting Model and the Effects Toward Children’s Akhlaq: An Ethnographic Study of Coastal Community in Padang West Sumatera - Zen, Auliya Rahmi; Zalnur, Muhammad; K, Munawir; Pratiwi, Yunita; Rambe, Anggi Afrina (International Journal of Islamic Studies Higher Education, 2022)
This study aims to identify how the parenting style of parents in instilling morality in children among the people on the coast. This study uses a qualitative method with an ethnographic approach, data sources were taken to eight informants consisting of five female parents (mother), and three parents (male) through in-depth interviews selected using purposive sampling technique. All interview results were then analyzed using Miles and Huberman's qualitative analysis technique with four steps of analysis (data collection, data reduction, presentation and conclusion). Overall, the research findings found that, there are three forms of parenting carried out by coastal community parents in educating children's morals in their daily lives. The three patterns are first; authoritarian parenting, second; democratic, third; permissive. The results of this study can be used as initial data for future research in examining different issues related to this problem and other issues relevant to this context.